Enhancing bone mineral density in osteogenesis imperfecta: The role of Zoledronate acid, vitamin D, calcium and phosphate - Hariroh, Nisa Afidatun; Perwitasari, Rayi Kurnia; Hisbiyah, Yuni; Rochmah, Nur; Setiawati, Rosy; Faizi, Muhammad (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Osteogenesis imperfecta (OI) is an uncommon genetic condition arising from type I collagen mutations, leading to bone fragility and recurrent fractures. Zoledronic acid is used to improve bone mineral density (BMD). The role of vitamin D, calcium, and phosphate in modulating BMD outcomes remains unclear. This study aimed to assess the effectiveness of zoledronic acid in increasing BMD in children with OI and its association with metabolic factors. Methods: A retrospective study was conducted on 24 children with OI in East Java. All patients received zoledronic acid (0.05 mg/BW) every 4–6 months for ≥1 year. Clinical data, fracture history, vitamin D, calcium, phosphate, and dual-energy X-ray absorptiometry (DXA) results at baseline and 2 years were analyzed using paired t-test, logistic regression, and correlation tests. Results: Most subjects were male, diagnosed at 20.0 ± 25.8 months, predominantly OI type III (95.8%). Mean treatment duration was 4.42 ± 2.69 years with a median of eight infusions. Absolute BMD (g/cm²) significantly increased at L1–4 (p=0.014), Total Body (p<0.001), and TBLH (p=0.013), though Z-score changes were not significant. Treatment cycles (OR=1.823;p=0.022) and duration (OR=2.572;p=0.022) predicted BMD improvement. Vitamin D (r=0.455;p=0.025) and calcium (r=0.484;p=0.017) correlated with Z-score BMD TBLH. Vitamin D deficiency was found0in 45.8% of patients. Conclusions: Zoledronic acid improves absolute BMD in children with OI, particularly with long-term treatment, Vitamin D status supports bone response, emphasizing combined pharmacologic and nutritional management.